Violence against children in humanitarian settings: A literature review of population-based approaches. (March 2016) - Stark, Lindsay; Landis, Debbie
Abstract: Children in humanitarian settings are thought to experience increased exposure to violence, which can impair their physical, emotional, and social development. Violence against children has important economic and social consequences for nations as a whole. The purpose of this review is to examine population-based approaches measuring violence against children in humanitarian settings. The authors reviewed prevalence studies of violence against children in humanitarian contexts appearing in peer-reviewed journals within the past twenty years. A Boolean search procedure was conducted in October 2014 of the electronic databases PubMed/Medline and PsychInfo. If abstracts contained evidence of the study's four primary themes – violence, children, humanitarian contexts and population-based measurement – a full document review was undertaken to confirm relevance. Out of 2634 identified articles, 22 met the final inclusion criteria. Across studies, there was varying quality and no standardization in measurement approach. Nine out of 22 studies demonstrated a relationship between conflict exposure and adverse health or mental health outcomes. Among studies that compared rates of violence between boys and girls, boys reported higher rates of physical violence, while girls reported higher rates of sexual violence. Children in infancy and early childhood were found to be among the most under-researched. Ultimately, the body of evidence in this review offers an incomplete picture regarding the prevalence, nature and impact of violence against children in emergencies, demonstrating a weak evidence base for some of the basic assumptions underpinning humanitarian practice. The development of standardized approaches to more rigorously measure violence against children is urgently needed in order to understand trends of violence against children in humanitarian contexts, and to promote children's healthy development and well-being. Highlights: Analyzes prevalence studies of violence against children (VAC) in emergencies. Reveals a lack of standard practice in measuring VAC in humanitarian emergencies. Shows limited evidence of whether and under what conditions VAC increases. Reveals fundamental assumptions underpinning VAC in emergencies are not data-driven.